Impact of surface-heterogeneity on atmosphere and land-surface interactions. (February 2017) - Liu, Shaofeng; Shao, Yaping; Kunoth, Angela; Simmer, Clemens
Abstract: Land-surface heterogeneity occurs on many scales, but its inclusion remains an unsolved problem in land-surface and atmospheric boundary-layer schemes for weather and climate models. We investigate the propagation of land-surface heterogeneity in a convective boundary layer using an atmosphere and land-surface coupled large-eddy model. Simulations are made for land surfaces of different heterogeneity scales and a uniform land surface. A multi-scale analysis is carried out and it is found that while domain-and-time averaged fluxes and state variables are not sensitive to land-surface heterogeneity, atmospheric patterns are. Close to the surface, atmospheric patterns are dominated by land-surface forced patterns; away from the surface, "eigen" patterns dominate and forced patterns reemerge for large averaging times. While small-scale land-surface features are more rapidly destroyed by turbulence, large-scale features can persist over hundreds of meters. Highlights: A model has been developed for atmosphere and land-surface coupled large-eddy simulation. Multi-scale wavelets analysis is used to study the propagation and persistency of land-surface patterns in the atmosphere. Instantaneous atmospheric patterns are insensitive to land-surface heterogeneity. Large spatial and longtime averaged atmospheric patterns are sensitive to land-surface patterns.